Study of Stock Ownership Nominee Agreement in Mining Business to People’s Welfare That Is Aligned for Sustainable Development Goals - Ida Sumarsih (Green Publisher Indonesia, 2024)
The goal for Limitation of Foreign Stock’s ownership to protect natural resources in Indonesia is not yet optimal because of the existence of nominee agreement. Which is a form of law smuggling. So natural resources that should be benefiting for Indonesia people’s welfare, in reality it is enjoyed by Foreign Investor. This research is a normatif juridical research using secondary data and doing inductive analysis. From the result of the research is concluded that law smuggling in stock ownership nominee agreement prohibition in mining field is still exist because there is no monitoring, control, field observation, evaluation and law enforcement for nominee agreement practices in mineral and coal mining up to beneficial ownership in establishment and operational of mineral and coal mining business. Therefore it is needed to make a regulation to monitor, supervise and doing law enforcement by The Energy and Mineral Resources Ministry (ESDM) through Monitoring, Conrolling, Field Observation and Evaluation System (P3LE) towards stock ownership nominee agreement practices in mining business so that the management of natural resources can be benefitting for poeple’s welfare and Sustainable Development Goals (SDGs) is achieved.